PENERAPAN MEDIA PEMBELAJARAN QUARTED CARD PADA MATERI ANCAMAN NEGARA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 1 BANCAR KABUPATEN TUBAN - Sulistyaningati; Listyaningsih; Supriyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This The purpose of this study was to improve the learning outcomes of students at SMAN 1 Bancar, Tuban Regency on state threats by using Quarted card learning media. The learning outcomes referred to in this study are the knowledge values ​​obtained by the post test. The type of research used is Classroom Action Research (CAR) with the Kurt Lewin model design. The data collection technique used was observation of students, tests and document analysis. The subjects of this study were in class X MIPA 3, totaling 37 people. Learning can be categorized as successful if the success rate is above 83% taken from the class competency achievement index (GPA). The results of this study indicate that the application of quarted card learning media to state threat material to improve student learning outcomes at SMA Negeri 1 Bancar, Tuban Regency is considered successful. Cycle 1 with an average value of 85.48 has a success rate of 75.68%. Cycle 2 has an average of 89.81 with a success rate of 94.6%. The conclusion from research on improving learning using quarted card media can improve student learning outcomes in the subject of state threats at SMA Negeri 1 Bancar.